Perancangan Inovatif Bagian Badan Robot Medis Militer dalam Pemilihan Material dan Efisiensi Struktur - Firmansyah, Muhammad Rheza; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2025)
This article discusses the innovative design of military medical robot bodies with an emphasis on selecting optimal materials and structures to improve durability and performance. Military medical robots are designed to support training activities and rescue operations. This study evaluated a number of materials, including carbon fiber, titanium, and composites selected based on strength, corrosion resistance, and ability to absorb impact. Additionally, the lightweight yet strong structure supports energy efficiency, allowing the robot to operate longer without needing frequent recharging. Tests show that the right combination of materials increases the robot's resistance to harsh terrain conditions and ensures the stability of the medical equipment inside. The selection of efficient materials and flexible structures in the body design of this military medical robot is expected to strengthen the effectiveness and safety for medical personnel and the TNI when operated.